Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario [infographie] - Consortium national de formation en santé; van Kemenade, Solange (2022)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)
Ce rapport a pour objectif de faire la mise à jour de recommandations tirées d’une étude réalisée par le Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) en 2017. Les actions comprennent, entre autres, l’identification de foyers pour l’offre de services en français ainsi que l'accompagnement de foyers pour l'amélioration des services en français et le développement de stratégies pour mettre en œuvre des soins culturellement adaptés. Dans le cadre de ce rapport, nous avons souligné les thèmes qui ont été partagés avec nous ou dont nous avons pris connaissance par l’entremise de notre travail avec nos partenaires. Le but est de capter l’essence de la réalité de l’expérience des francophones résidant dans les foyers de soins de longue durée, ainsi que d’offrir des pistes d'actions qui nous permettront d’assurer une meilleure planification des services en français dans les foyers de soins de longue durée dans le Nord de l’Ontario.

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)
The purpose of this report is to provide an update on the recommendations from a study completed by the Réseau du mieux-être francophone du Nord de l’Ontario (Réseau) in 2017. The actions include identifying homes where French-language services could be offered, accompanying those homes where French-language services could be improved and developing strategies to implement culturally appropriate care. In the context of this report, we have identified themes that were shared with us or that we became aware of through working with our partners. The goal is to capture the essence of the real experience of Francophone residents in long-term care homes as well as offer courses of action which will allow us to ensure better planning of French language services in long-term care homes throughout Northern Ontario.

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.